Association between employees' perception towards workplace learning and learning outcome in selected SMEs - Lim, Agnes Siang Siew (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The focus of this study is to identify the association between employees' perception towards workplace learning and learning outcome in the selected Small and Medium enterprises (SMEs). Apart from that, the study also aim to identify the most preferable type of workplace learning activities in the SMEs related to metal products. Survey questionnaire is utilized as the instrument for data collection.